The scopes, outcomes, and limitations of health trials on oral sex practices: a global scoping review - Kafayat Aminu; Timothy Olukunle Aladelusi; Afeez Abolarinwa Salami; Semeeh Akinwale Omoleke; Chiamaka Norah Ezeagu; Julienne Murererehe; Charles Adetokunbo Olomo; Jimoh Amzat; Peace Uwambaye; Akinyele Olumuyiwa Adisa; Kehinde Kazeem Kanmodi (BMC Public Health)
Abstract Background Due to the persistently rising prevalence of oral sex practices across the world, oral sex is now a global health issue. So far, different health trials have been conducted in an attempt to curb the health risks associated with oral sex practices. However, no known study has mapped the scope, outcomes, and limitations of these trials. Hence, this global scoping review aimed to map the existing evidence. Methods This scoping review was reported using the PRISMA-ScR guidelines. On 7th April 2024, we conducted a systematic search of eight research databases and reviewed all trials that met the review’s inclusion criteria. The narrative synthesis approach was used in the collation, summarization, and reporting of the data extracted from the included trials. Results Only 15 relevant articles were included in the review and 11 of these were conducted in the USA. 33% of the reviewed studies employed a randomized control trial (RCT) design. None of the reviewed trials focused solely on oral sex practices, as they also investigated other sexual practices. The sample size of the reviewed trials ranged between 80 and 1543 with an average sample size of 506.7 per trial, while 53% of the trials focused on women and girls. Only six of the 15 trials reported baseline sexual behaviour which showed the heterogeneity of risky sexual practices, including oral sex, in different populations and contexts. Regarding behavioural modifications post-intervention, findings from the review mostly noted modification to sexual behaviours in the intervention groups, signifying intervention efficacy. However, common limitations of the reviewed trials, include reliance on self-reported data without other means of verification, limited generalizability of findings and short or no follow-up periods. Conclusion Worldwide, there is a paucity of health trials on oral sex practices. Despite methodological limitations, these trials reported mixed results, with the majority demonstrating positive changes in attitudes towards oral sex. Finally, there is a need for multi-country RCTs that are focused on oral sex practices, to ensure future policies related to oral sexual health are based on trials that are more rigorous, credible, and generalizable.